Associations between neutrophil-lymphocyte ratio with all-cause mortality, major adverse vascular events and progression of diabetic kidney disease in type 2 diabetes mellitus - Chee, Ying Jie; Zhang, Xiaoe Doris; Dalan, Rinkoo (Frontiers in Endocrinology, 2025)
IntroductionThe neutrophil lymphocyte ratio (NLR) is a readily accessible marker of systemic inflammation. This study evaluated the association between NLR with all-cause mortality, major adverse vascular events and diabetic kidney disease (DKD) progression in a multiethnic cohort of adult type 2 diabetes mellitus (T2DM) individuals in Singapore.MethodsDemographic, anthropometric, biochemistry, mortality and major adverse vascular events (MAVE) were obtained from electronic medical records up to June 30, 2024. Composite renal outcomes were defined as one of the following: decline in eGFR ≥ 40%, decline in eGFR to ≤ 15ml/min/1.73m2 or initiated maintenance dialysis. Multivariate Cox regression analyses were performed to evaluate associations between NLR, all-cause mortality, MAVE and composite renal outcomes.ResultsIn this cohort of 959 adult participants with T2DM, there was a significant association between NLR with all-cause mortality, MAVE, baseline albuminuria, renal function and progression of DKD. During the median follow-up of 9.4 years, there were 367 (38.3%) mortalities, 222 (23.1%) cases of MAVE and 285 (30%) participants who developed a renal outcome. The highest NLR was associated with a 1.6-fold increased risk for all-cause mortality (HR 1.63; 95% 1.18 - 2.27, p=0.003), 2.7-fold increased risk of MAVE (HR 2.71; 95% CI 1.75 - 4.20; p<0.001) and 1.55 (HR 1.55, 95% CI 1.09 - 2.19, p=0.014) increased risk of having a renal event compared to the lowest NLR tertile after adjusting for confounders.ConclusionElevated NLR is independently associated with all-cause mortality, MAVE and composite renal outcomes in T2DM. NLR may be considered a potential clinical biomarker of adverse outcomes for use in routine care.